Effects of caffeine on exercise performance, lactate, f.f.a., triglycerides, prolactin, cortisol and amylase in maximal aerobic exercise - Peker, I.; Gören, Z.; Çiloglu, F.; Karacabey, K.; Ozmerdivenli, R.; Saygın, Ö. (My University, 2005)
In this study the effect of caffeine (5 mg/kg) on maximal power output, lactate, blood FFA, triglyceride, amylase, prolactin and cortisol hormones was examined during a 20 m. progressive shuttle-run test at the same time of day, one week apart. Subjects were twenty male, elite, long distance athletes aged between 19–30. In each of the trials, solutions were given one hour prior to testing by Appling a single blind experimental design. Statistical analysis was carried out on the relevant data using Student's T-tests. Caffeine trial was compared with the placebo. MaxVO2 values, which reflects sportive performance of the sportsman, during exercise and all parameters before exercise were not significantly different between caffeine and placebo trials (P>0.05). After exercise (6min.), values were as fallows. Systolic blood pressure values were found to be significantly higher (P=0.02) whereas blood lactic acid values were lower (P=0.01) in the caffeine trials. Heart rate, diastolic blood pressure, FFA, triglycerides, amylase, cortisol, and prolactin concentrations were not significantly different between the trials (P>0.05). As a conclusion these results suggest that orally taken caffeine amounts of 5 mg/kg or less does not affect exercise performance and are not effective as a doping substance. © 2005 Taylor and Francis Group, LLC.
Keywords: amylase; caffeine; fatty acid; hormone; hydrocortisone; lactic acid; placebo; prolactin; triacylglycerol; adult; aged; article; athlete; blood; diastolic blood pressure; doping; exercise; experimental design; fallow; heart rate; human; human experiment; lactate blood level; male; normal human; performance; sport; statistical analysis; statistical significance; Student t test; systolic blood pressure